(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The French colonization of Vietnam had a significant impact on Vietnamese history, social structure and spiritual life. This study is based on the fact that the presence of the colonizers changed and ruptured Vietnamese cultural tradition. As a result, generations of Vietnamese people attempted to rebuild their identity through various means with the aim to adapt to new conditions, and one of which was composing historical novels. The research provides a brief overview of the settings of colonial Vietnam in the early twentieth century. It is obvious that because of its complicatedness, the article only indicates its general traits, considering them important premises upon which our study of Vietnamese literature of the time is based. I then present how Southern Vietnamese writers made use of their historical novels to evoke the public sense of nationalism and construct the notion of unified origin. Southern Vietnamese literature is chosen to be studied since this is a special territory where different cultural and political issues concerning the making of modern Vietnam came up.